1987
DOI: 10.1128/mcb.7.5.1856
|View full text |Cite
|
Sign up to set email alerts
|

Albumin and alpha-fetoprotein gene transcription in rat hepatoma cell lines is correlated with specific DNA hypomethylation and altered chromatin structure in the 5' region.

Abstract: We examined DNA methylation and DNase I hypersensitivity of the a-fetoprotein (AFP) and albumin gene region in hepatoma cell lines which showed drastic differences in the level of expression of these genes. We assayed for methylation of the CCGG sequences by using the restriction enzyme isoschizomers HpaH Many studies with different experimental systems have been carried out to elucidate the role that methylation of cytosine bases and change in chromatin structure might play in the regulation of gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…There was no evidence that the -3.5-kb region could function as an enhancer. Previous studies found a liver-specific hypersensitive site 2.8 kb upstream of the rat albumin promoter (Babiss et al 1986;Turcotte et al 1986;Nahon et al 1987;Tratner et al 1987); this site is in a position similar to the site found at -3.5 kb in mice by Pinkert et al (1987) and in this study. Rodent hepatoma cell lines transcribe the al bumin gene at a much lower rate than liver (Clayton et al 1985b); in such cells the gene is weakly hypersensi tive at the promoter, and not at all at the expected -2.8-kb (Babiss et al 1986;Nahon et al 1987) or -3.5-kb (Y. Bergman and K. Zaret, unpubl.…”
Section: Genes and Developmentsupporting
confidence: 64%
“…There was no evidence that the -3.5-kb region could function as an enhancer. Previous studies found a liver-specific hypersensitive site 2.8 kb upstream of the rat albumin promoter (Babiss et al 1986;Turcotte et al 1986;Nahon et al 1987;Tratner et al 1987); this site is in a position similar to the site found at -3.5 kb in mice by Pinkert et al (1987) and in this study. Rodent hepatoma cell lines transcribe the al bumin gene at a much lower rate than liver (Clayton et al 1985b); in such cells the gene is weakly hypersensi tive at the promoter, and not at all at the expected -2.8-kb (Babiss et al 1986;Nahon et al 1987) or -3.5-kb (Y. Bergman and K. Zaret, unpubl.…”
Section: Genes and Developmentsupporting
confidence: 64%
“…An extensive amount of work, however, has established the paradigm that active genes reside in open chromatin. This has been demonstrated for many endogenous loci (12,17,29,40) and also has basis in a history of cytogenetic evidence (2,24). Therefore, we favor the interpretation that the observed level of expression and rearrangement from the unmethylated transgene represents leak-through rather than bona fide activity.…”
Section: Discussionmentioning
confidence: 82%
“…We find that the segment of rat AFP DNA spanning -1.2 to -4 kb from the AFP transcription initiation site is a typical enhancer, sufficient to confer high activity upon the AFP promoter in well-differentiated hepatoma cells. The active components of this enhancer element lie between -2.2 and -4 kb and match the only two DH sites in the 7-kb domain upstream from the AFP promoter in rat liver chromatin (32,42,44). Transgene and transfection assays leave ambiguities on liver-specific functions of the AFP enhancer domain, one reason being that segments of DNA between -4 and -7 kb can substitute for the downstream enhancer segments in transfected hepatocytes (17, 31; our unpublished results) or transgenic livers (22).…”
Section: Discussionmentioning
confidence: 99%
“…A promoter domain spanning '230 nucleotides comprises a chromatin DNase I-hypersensitive (DH) site (32, 42,44) that is selectively suppressed by dexamethasone (44), glucocorticoid receptor recognition sequences, and octamer motifs similar to those present in other genes under developmental and growth control (8). A distal domain (-2 to -4 kilobases [kb] relative to the AFP transcription initiation site) is comprised of a liver-constitutive DH site and a developmental stagespecific DH site (32,42,44). These structural features may suggest a cooperativity between distal regulatory elements * Corresponding author.…”
mentioning
confidence: 99%